Causal recipes sufficient for identifying market gurus versus mavens - Chung, M.; Woodside, Arch (2012)
Prior research focusing on the market maven (MM) neglects to consider the possible existence of people who may represent an important source of marketplace information for MMs-the market guru (MG). A "market guru" is a consumer others frequently seek out for advice but who does not seek advice from others. In contrast to MG, a MM is a consumer who other consumers frequently ask for advice and who frequently seeks advice from others. This study raises the proposition that a greater share of MGs versus MMs are innovators, that is, individuals who rely on technical reports to become the first to adopt new products in her or his community. This study applies fuzzy-set qualitative comparative analysis (fs/QCA) to distinguish between MMs and MGs using multi-year data from a national U.S. omnibus survey. The findings support several propositions distinguishing MGs from MMs. MMs evaluate themselves as great influencers of consumers, highly sensitive to normative susceptibility, and possessing superior taste. However, MGs evaluate themselves exactly the opposite from MMs on these conditions. © 2012, IGI Global.